MHCquant2 refines immunopeptidomics tumor antigen discovery - Scheid, Jonas; Lemke, Steffen; Hoenisch-Gravel, Naomi; Dengler, Anna; Sachsenberg, Timo; Declerq, Arthur; Gabriels, Ralf; Bauer, Jens; Wacker, Marcel; Bichmann, Leon; Martens, Lennart; Dubbelaar, Marissa L.; et al. (Genome Biology, 2025)
Confident identification of human leukocyte antigen (HLA)-presented peptides is crucial for advancing cancer immunotherapy. We present MHCquant2, a scalable and modular Nextflow pipeline integrated into nf-core as a reproducible, portable, and standardized workflow for immunopeptidomics. This integration allows a community-driven, robust solution for high-throughput analyses across operating systems and cloud infrastructures. MHCquant2 integrates open-source tools including OpenMS, DeepLC, and MS 2 PIP, improving peptide identifications by up to 27% across diverse MS platforms, particularly enriching low-abundant peptides. MHCquant2 demonstrates state-of-the-art performance on our novel benign MHCquant2 dataset ( n = 92) and expands the benign human immunopeptidome by over 160,000 unique naturally presented HLA peptides.